Investing Strategy Using Technical Analysis: A Case of Infosys - Sane, Sandip (Indian Journal of Finance, 2012)
The forces of supply and demand result from two powerful emotions: demand results from the hope for profits; supply results from the fear of loss. When these two opposing forces are not in balance, stock prices move up if the demand side is greater, and down if the supply side is greater. In the present paper, the researcher has analyzed the charts of the INFOSYS stock for the period from April 2011 to September 2011 and has used various technical Analysis Tools in predicting the trend so as to take informed decision in holding, buying, or selling the shares. The researcher has used candle stick charts and tools like EMA, Price Patterns, Stochastic, MSD, RSI, Bollinger Band, Resistance and Support to evaluate the Infosys Share.